PERILAKU PENGUSAHA BUS PARIWISATA SEBAGAI KONSUMEN RASIONAL SELAMA PANDEMI COVID-19 - Nurzahroh Lailyah; Tina Rahayu; Keke Tamara Fahira (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This study aims to analyze rational consumer behavior during the Covid-19 pandemic. The research method used is qualitative research with a case study approach. Data collection techniques were obtained from observations, interviews, and documentation. The data validity technique used by researchers was source triangulation with analytical procedures including data reduction, data display, drawing conclusions and verification. The results of this study indicate that there is a change in the consumption behavior of tourism bus entrepreneurs from being consumptive to being more rational during the Covid-19 pandemic. Rational behavior in this study is measured based on need, capability, best quality, and optimal utility.